The Effect of History Teaching Supported by Dramatization Technique on Students’ Achievement and Permanence Level - Karabag, S. Gulin; Aydogan, Okan (Asian Journal of Education and Training, 2021)
The aim of this study is to determine the effect of history teaching supported by dramatization technique on students’ success and permanence in history education in comparison with the traditional teaching. In this research, the semi experimental method which was practiced by pre-test, post-test and permanence test were used and it was studied on two different student groups. One of them is control group tested with lecture method and the other one is experimental group tested by dramatization technique. Tested group consists of 63 students who studying in classes 10-A and 10-B of a vocational high school of Kırıkkale. This study is limited with units of “From Principality to State” in 10th grade students. During this experiment containing retention test were applied to experimental and control groups and the results were analyzed by the program SPSS 16.0. According to the findings obtained, in history lesson: there is a significant difference between the points of success and permanence of the group which is tested by dramatization technique and the group which is tested by teacher centered teaching. In other words, the dramatization technique, which actively involved students in the learning environment, was found to be more effective in the educational success of students and permanence of the information they learned compared to the teacher centered approach on the transfer of historical information to the students.